Power of unweighted and weighted versions of simultaneous and sequential multiple-comparison procedures.[article]. - Klockars, Alan J.
The authors investigate the relative power of unweighted and weighted versions of simultaneous and sequential Bonferroni procedures. The unweighted simultaneous procedure is represented by the standard Bonferroni; the unweighted sequential methods are from S. Holm (1979) and G. Hommel (1988); the weighted simultaneous procedure comes from R. Rosenthal and D. B. Rubin (see record 1984-05701-001); and the weighted sequential method is also from S. Holm. These are applied to a complete set of C = 3 orthogonal contrasts defined by 4 treatment groups. The authors present power estimates for small, medium, and large effects in various effect and weighting configurations. They discuss factors affecting the relative power of these methods and present statistical evidence that strengthens a case against weighted procedures built on methodological subjectivity issues. -- (from the author)